Mechanism of Transplanted Islet Engraftment in Visceral White Adipose Tissue. Issue 12 (December 2020) - Sakata, Naoaki; Yoshimatsu, Gumpei; Tanaka, Tomoko; Yamada, Teppei; Kawakami, Ryo; Kodama, Shohta
Abstract : Background: White adipose tissue (WAT) is a candidate transplantation site for islets. However, the mechanism of islet engraftment in WAT has not been fully investigated. In this study, we attempted to clarify the therapeutic effect and mechanism of islet transplantation into visceral WAT. Methods: Two hundred mouse islets were transplanted into epididymal WAT of syngeneic diabetic mice by wrapping islets with the tissue (fat-covered group). Mice that received intraperitoneal and renal subcapsular islet transplantations were used as negative and positive control groups, respectively. Results: The transplant efficacy, including improvements in blood glucose and plasma insulin levels and in glucose tolerance tests, of the fat-covered group was superior to the negative control group and almost equal to the positive control group. Vessel density of engrafted islets in the fat-covered group was higher than that in the positive control group. It was speculated that the mechanism of islet engraftment in WAT might consist of trapping islets in WAT, adhesion of islets via a combination of adhesion factors (fibronectin and integrin β1), and promotion of angiogenesis in islets by expression of angiogenic factors induced by adiponectin. Conclusions: Visceral WAT is an important candidate for islet transplantation. Adhesion factors and adiponectin might contribute to islet engraftment into WAT. Further studies to elucidate the detailed mechanism are necessary. Abstract : Supplemental Digital Content is available in the text.